Validasi Dan Verifikasi Hasil Uji Sun Protection Factor (Spf) Pada Sediaan Sunblock Dan Sunscreen Bermerk Dengan Metode Spektrofotometri - rahayu artini yuan (Universitas Muhammadiyah Surabaya, 2020)
Tests for the determination of SPF value were calculated from the seven sunblock and brandes sunscreen preparation which were analyzed using 96% etanol solvent and kloroform, ranging from 17.21-26.88. The results of the VA-14 sample calculation have the lowest SPF value (SPF = 17.21) and the ES-30 sample has the largest SPF value calculation results from the seven samples (SPF ES-30 = 26.88). The seven samples are samples that have well-known brands in Indonesia. Of the seven cosmetics samples, six samples had a% recovery in accordance with the standard between 80-120%, but one product, namely SA-35, had a recovery rate of 73.23%. Organoleptic test results showed that the overall type of cream was m / a, fragrance, color from milky white, light brown, and light green. The pH value between 6.8-7.5 according to the quality standard of sunscreen preparations in SNI 16-4399-1966, the pH value for sunscreen preparations is 4.5-8.0. Thus, the results of the seventh pH of the sample are still within good standard limits for cream preparations containing sunscreen.